Efficient Management of Municipal Enterprises - Narmania, Davit (European Journal of Multidisciplinary Studies, 2018)
Municipal enterprises, as the local service providers, require a specific management approach. On the one hand, the municipal enterprises are organizations based on a certain commercial basis like LTD, Joint Stock Company and etc. and on the other hand, they have a different style of governance (e.g. municipal supervisory board). Additionally, the sources of budget formation are also different. They can have municipal funding as well as tariffs and commercial revenues. Planning, organizing, motivating and controlling management tools are used in municipal enterprises, like in commercial organizations. However, the implementation tools and functional subsystems are different (HR, communication, marketing, financial and operational management). Municipal enterprises are often required transparency, accountability and more corporate social responsibility than the private ones. This is caused by the fact that the municipal services are directly used by the citizens and in some cases, they are financed by civilians’ taxes. Nowadays there are debates if public or private enterprises provide more valuable services (higher quality goods at a lower price) for citizens. Furthermore, if a private company is operating better, it creates possibility to privatize the public enterprise. However, in our work it won’t be discussed. The main purpose of the paper is to determine the main postulates that will increase the efficiency of existing municipal enterprises. Accordingly, possible instruments are discussed in order to deliver public services, which have higher quality, are accessible and relatively inexpensive. In the paper theoretical and several practical examples of Georgia are discussed in order to improve municipal enterprise management efficiency.